ANALISIS NILAI KONSERVASI TINGGI ASPEK SOSIAL EKONOMI BUDAYA MASYARAKAT (Studi Kasus Distrik Moisigin Kabupaten Sorong, Provinsi Papua Barat) - Maliki , Muhammad Anjal Firman; Susdiyanti, Tun; Karlina, Endang (Jurnal Nusa Sylva, 2022)
High Conservation Values ​​(HCV) are important social and environmental values ​​in ecosystems and landscapes that are jointly identified by long-term multi-stakeholder processes as important values ​​that must be conserved in the management of natural systems. The variety of forest ecosystem services that can be utilized makes the people of the Moisigin District, Sorong Regency, West Papua Province dependent on the forest for their daily lives. The research was conducted in three villages in the Moisigin District, namely Klasof, Klafdalim and Ninjimor villages. The aim of the study was to identify the conservation value in the socio-economic aspects of culture and to determine the level of community dependence on forest areas in the Moisigin District, Sorong Regency, West Papua Province. This study used a survey research method, determined the respondents by Proportional Random Sampling, with the number of respondents was 81 people, and analyzed descriptively. The results showed that forest areas in the Moisigen District, namely Klasof village and Klafdalim village had HCV 5 in the form of the Klasof water reservoir, the border the Modan river and the Tadalim riverbank, while Ninjimor village has HCV in the form of the Masinau Marga sago plantation and HCV 6 in the form of the Matawol sacred forest. The level of community dependence on the forest area of ​​Klasof village is 38%, Klafdalim village is 29.7% and Ninjimor village is 45% or is included in the Forest Dependent category.